Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - Chapter 1 Review Problem Set: 68

Answer

$-44$

Work Step by Step

Substituting $a= 2 $ and $b= -5 ,$ the given expression, $ 2ab-3(a-b)+b+a ,$ evaluates to \begin{array}{l}\require{cancel} 2(2)(-5)-3(2-(-5))+(-5)+2 \\\\= -20-3(2+5)-5+2 \\\\= -20-3(7)-5+2 \\\\= -20-21-5+2 \\\\= -41-5+2 \\\\= -46+2 \\\\= -44 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.